Stress in Dentistry: A Review - Marlin Jena1 , Dharmashree Satyarup2 , Ramesh Nagarajappa3 , Upasana Dhar1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Dentists are prone to have different kinds of mental, physical, psychological and financial complicationsrelated to stress. It is important for the dentists to de-stress themselves by a reduction in the number ofstressors and increase the ability to deal with stressful situations. The practices like resisting stress as wellas time management and choosing goals which are similar to real-life scenario should be encouraged. Sothat stress can be reduced to a tolerable level. Like any profession, the transition from academics to theworkplace could be a challenging task. As it is known that dental care professionals have responsibility forthe health status of general people. So,there is a need for stress management and reduction programs to beintegrated into dental education, which can provide practical solutions for curtailing various types of stress.Here we will know how to promote and enhance the well-being of the dentists by understanding the valueof life.